Strategic Arms Limitation Talks (SALT): an ethical or political problem - Nwoye Leonard; Mfonobong David Udoudom; Samuel Akpan Bassey (Center for Humanities and Innovation Studies, 2019)
It is a known fact that Strategic Arms Limitation Talks and other related talks on nuclear arms disarmament have failed to achieve a nuclear arms agreement among nations that will lead to nuclear-free World. It is almost impossible to accomplish this single task for more than 71 (seventy-one) years. Every scholar in the globe has an opinion towards nuclear arms limitation talks. It is tricky to say whether or not SALT is an Ethical or Political problem? This paper tries to answer this question. As a result, it is incorrect to treat nuclear weapons control, which exists in the realms of 'ought,' as a scientific or political problem that exists in the realm of 'is.' Moral expressions are in the regions of 'ought' above every fact and science, custom and tradition, despite the existence of several ethical systems.